Isolation of Elizabethkingia anophelis From COVID-19 Swab Kits - Xu, Liangcai; Peng, Bo; He, Yuxiang; Cui, Yujun; Hu, Qinghua; Wu, Yarong; Chen, Hongbiao; Zhou, Xiaofeng; Chen, Lili; Jiang, Min; Zuo, Le; Chen, Qiongcheng; et al. (Frontiers in Microbiology, 2022)
Purpose: To investigate and characterize the putative Elizabethkingia anophelis contaminant isolated from throat and anal swab samples of patients from three fever epidemic clusters, which were not COVID-19 related, in Shenzhen, China, during COVID-19 pandemic. Methods: Bacteria were cultured from throat (n = 28) and anal (n = 3) swab samples from 28 fever adolescent patients. The isolated bacterial strains were identified using matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF/MS) and the VITEK2 automated identification system. Nucleic acids were extracted from the patient samples (n = 31), unopened virus collection kits from the same manufacturer as the patient samples (n = 35, blank samples) and from unopened throat swab collection kits of two other manufacturers (n = 22, control samples). Metagenomic sequencing and quantitative real-time PCR (qPCR) detection were performed. Blood serum collected from patients (n = 13) was assessed for the presence of antibodies to E. anophelis. The genomic characteristics, antibiotic susceptibility, and heat resistance of E. anophelis isolates (n = 31) were analyzed. Results: The isolates were identified by MALDI-TOF/MS and VITEK2 as Elizabethkingia meningoseptica. DNA sequence analysis confirmed isolates to be E. anophelis. The patients’ samples and blank samples were positive for E. anophelis. Control samples were negative for E. anophelis. The sera from a sub-sample of 13 patients were antibody-negative for isolated E. anophelis. Most of the isolates were highly homologous and carried multiple β-lactamase genes (blaB, blaGOB, and blaCME). The isolates displayed resistance to nitrofurans, penicillins, and most β-lactam drugs. The bacteria survived heating at 56°C for 30 min. Conclusion: The unopened commercial virus collection kits from the same manufacturer as those used to swab patients were contaminated with E. anophelis. Patients were not infected with E. anophelis and the causative agent for the fevers remains unidentified. The relevant authorities were swiftly notified of this discovery and subsequent collection kits were not contaminated. DNA sequence-based techniques are the definitive method for Elizabethkingia species identification. The E. anophelis isolates were multidrug-resistant, with partial heat resistance, making them difficult to eradicate from contaminated surfaces. Such resistance indicates that more attention should be paid to disinfection protocols, especially in hospitals, to avoid outbreaks of E. anophelis infection.